Social responsibility and the competitive bid process for major sporting events - Carey, M.; Mason, D. S.; Misener, L. (Journal of Sport and Social Issues, 2011)
The 2016 Summer Olympic Games bids were selected as a case study to explore how the focus on social responsibility (CSR) and community development (CD) differs in traditional versus nontraditional bid cities. We employed a media framing methodology to examine how the bids were represented through media and articulated by various stakeholders. Of specific interest was the finding that the discourse surrounding the Rio de Janeiro bid put a greater focus on the capability of sport to reach out to disadvantaged populations and create balance within the global economy. The results from this study will provide insights into how the global media has framed megaevent bids from nontraditional cities, and the social and economic benefits event proponents argue can be accrued from hosting.